Pengembangan Kapasitas Usaha Kecil Menengah Dalam Memanfaatkan Sistem Hak Kekayaan Intelektual Bagi Peningkatan Daya Saing Usaha - Suryasaladin, Ranggalawe (Jurnal Hukum & Pembangunan, 2020)
As a main contributor to Indonesia GDP, Small and Medium Enterprises should be assisted by Goverment and University in order to expand its capacity in managing their intangible assets and intellectual property. The efforts in giving guidance to SMEs in managing its IP and take a benefit of IP systems could be on the mapping of problems faced by SMEs in managing its IP and addressing a better policy recommendation suitable to solves it problems. This article streghtening the arguments that to enhance Indonesia SME capacities in managing its IP , the government institutions and university have to coopertate in disseminating IP strategy adaptive to the needs and challenges faced by SMEs of Indonesia in protecting its IP assets, enforcing, and commercialization of its IP assets.